Inducing secondary metabolite production by the endophytic fungus Chaetomium sp. through fungal–bacterial co-culture and epigenetic modification. Issue 41 (13th October 2016) - Akone, Sergi Herve; Mándi, Attila; Kurtán, Tibor; Hartmann, Rudolf; Lin, Wenhan; Daletos, Georgios; Proksch, Peter
Abstract: Co-culturing the fungal endophyte Chaetomium sp. with the bacterium Bacillus subtilis on solid rice medium resulted in an up to 8.3-fold increase in the accumulation of constitutively present metabolites that included a 1:1 mixture of 3- and 4-hydroxybenzoic acid methyl esters (1 and2, respectively), and the polyketides acremonisol A (3 ), SB236050 (4 ), and SB238569 (5 ). In addition, seven compounds including isosulochrin (6 ), protocatechuic acid methyl ester (7 ), as well as five new natural products (8 –12 ) were detected in the co-cultures, but not in axenic fungal cultures. Treatment of Chaetomium sp. with the epigenetic modifier suberoylanilide hydroxamic acid or 5-azacytidine resulted in an enhanced accumulation of6, which was likewise detected during co-culture. Compound5 showed strong cytotoxicity against the mouse lymphoma L5178Y cell line with an IC50 value of 1 μM, as well as weak antibacterial activity against B. subtilis with an MIC value of 53 μM. Graphical abstract: